MODERASI DALAM PERBEDAAN PENENTUAN AWAL BULAN RAMADAN, SYAWAL DAN DZULHIJJAH DI INDONESIA: Analisis Fikih Ikhtilaf dan Kebijakan Hukum Keagamaan - Ahmad Wahidi; Hisbulloh Hadziq (Mitsaq: Islamic Family Law Journal, 2026)
Differences in determining the beginning of Ramadan, Shawwal, and Dzulhijjah are a recurring phenomenon in the religious practices of Muslims in Indonesia. These differences are primarily influenced by variations in the methods used, namely rukyatul hilal and hisab, as well as differences in the interpretation of sharia arguments and the ijtihad approaches of scholars. This study aims to analyze the diversity of determinations of the beginning of Islamic months in Islamic jurisprudence and explain how these differences are managed through a religious moderation approach. This study is a normative study with a qualitative approach, using library data in the form of fikih literature, hadith, the views of scholars of various schools of thought, and government policies related to determining the beginning of Islamic months. The results show that differences in determining the beginning of Islamic months are a matter of ijtihadiyah that is furu'iyyah and inevitably occurs in the Islamic legal tradition. Therefore, these differences cannot be positioned as a source of conflict, but rather as a form of the richness of Islamic scientific treasures. A moderate religious approach is an important tool in managing differences, emphasizing the values ​​of inclusivity, dialogue, justice, and respect for authority, as well as diversity of opinion. Thus, the diversity in determining the beginning of Islamic months can be directed towards strengthening social harmony and unity of the community, without negating the religious beliefs and practices of each group. Specifically, the findings of this study are intended to serve as a basis for consideration by the government, Islamic civil society organizations, and stakeholders in establishing a more inclusive, dialogue-based governance framework for determining the start of the Islamic month—one oriented toward the public interest of the Muslim community. More broadly, the study aims to provide Indonesian Muslims with insights into how to approach the diversity of methods used to determine the beginning of the Islamic month.